Research Progress on Dynamic Response Mechanism and Damage Control of Jointed Rock Mass Blasting - Luo, Xinyue; Yu, Qingyang; Liu, Dong; Dai, Zhenxue (Journal of Research in Science and Engineering, 2025)
The dynamic response of jointed rock masses under blasting loads is a critical scientific issue for safe and efficient tunneling and mining engineering. This paper systematically reviews the synergistic mechanisms between blast stress waves and gas propelling agents in rock fragmentation, elucidating how joints regulate energy propagation, crack propagation, and damage evolution during blasting. Research findings indicate that joints enhance blasting responsiveness through three mechanisms: reflecting/transmitting stress waves, altering crack propagation directions, and dissipating energy to amplify anisotropy; gas propelling agents drive quasi-static crack propagation, while joint length and orientation control the “guidance-suppression” effect on crack development; coupled high stress-joint interactions intensify rock mass damage zoning. Through numerical simulations (LS-DYNA/RHT models), experimental studies (dynamic dissipation line technique, CT reconstruction), and engineering practices, this paper proposes recommended blasting parameter design and damage control strategies. Future research should focus on multi-field coupling models, intelligent algorithms, and blasting theories under complex deep geological conditions, advancing rock mass blasting from empirical design to precision engineering.